Do We Have Baby Boomers, Gen X And Gen Y? A Preliminary Study To Explore Generation Cohorts In Malaysia - Ernest Cyril, de Run; Hiram, Ting; Lim, Tze-Yin; Koh, Hannah; Murni, Sahdan (2016)
Notwithstanding the prevalence use of generation labels and descriptions from the U.S. sources in marketing literature and segmentation practices in Malaysia, there is an extreme lack of studies that justify such adoption with theoretical support and empirical evidence. The present preliminary study is performed to explore generation cohorts in Malaysia by using sociological theories of generations as the underpinning basis. The purpose is to identify the major external events which have impacted Malaysians during their formative years and define actual generation cohorts in the Malaysian context. A qualitative approach via personal interview was administered. 80 nationwide interviews were conducted and audiorecorded. The data were then transcribed and analyzed using content analysis with the aid of ATLAS.ti. The findings suggest that the experiences of external events which Malaysians have are different from the experiences of the U.S. population. As such, five generation cohorts are proposed based on the collective experience of those who are born during the same period of time and distinctive experience of those who are born at different times during their formative years respectively. The study not only unearths actual Malaysian generation cohorts, it also pioneers future investigation pertaining to generation cohorts in Malaysia and the use of generations in various studies and practices.